Carbon composite nickel / cobalt / zinc entropy-doped sodium ferric phosphate material as well as preparation method and application thereof

Through medium-entropy doping and carbon composite technology, carbon composite nickel/cobalt/zinc medium-entropy doped sodium phosphate material with high electrochemical properties was prepared, which solved the problems of low cyclic stability and electronic conductivity of the positive electrode materials of existing sodium ion batteries, and achieved rapid and stable sodium storage performance and industrial applicability.

CN119822345APending Publication Date: 2025-04-15武汉启钠新能源科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411978650.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have poor cycle stability, low electronic conductivity, and are prone to form heterophasic NaFePO4 during the preparation process, which limits its industrial promotion.

Method used

The carbon composite nickel/cobalt/zinc medium-entropy doped sodium iron phosphate material is prepared by using medium-entropy doped combined with carbon composite. Through spray granulation and high-temperature calcination processes, a porous bowl-like structure is formed to improve electron conductivity and inhibit the formation of heterophase NaFePO4.

Benefits of technology

It significantly improves the electrochemical performance of composite materials, improves redox activity, electronic conductivity and Na diffusion channels, achieves rapid and stable sodium storage performance, and simplifies the preparation process, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005221011740000011
    Figure HDA0005221011740000011
  • Figure HDA0005221011740000012
    Figure HDA0005221011740000012
  • Figure HDA0005221011740000021
    Figure HDA0005221011740000021
Patent Text Reader

Abstract

The invention discloses a carbon composite nickel / cobalt / zinc entropy-doped sodium ferric phosphate composite material, the stoichiometric formula of the composite material is Na < 4 > Fe < 3-3x > Ni < x > Co < x > Zn < x > (PO4) < 2 > P < 2 > O < 7 > / C, and the value of x is 0.02-0.04; a carbon source, a sodium source, an iron source, a nickel source, a cobalt source, a zinc source and a phosphorus source are used as main raw materials, and mixed dispersion liquid is sequentially subjected to ball milling, sand milling, spray granulation and recrystallization high-temperature calcination to prepare the catalyst. According to the invention, a strategy of medium entropy doping and carbon compounding based on nickel, cobalt and zinc is adopted, and processes of spray granulation, high-temperature calcination and the like are combined, so that diffusion channels of sodium ions can be effectively realized, the electron transmission efficiency can be improved, the stability of a primary material structure can be improved, and the problem of impurity phases of NaFePO4 can be inhibited; the composite material is used as a sodium ion battery positive electrode material, can show relatively good rate capability, cycling stability and the like, and is suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy materials, and specifically relates to a carbon composite nickel / cobalt / zinc medium-entropy doped sodium iron phosphate material and a preparation method and application thereof. Background Art

[0003] Positive electrode materials play a key role in the development of sodium-ion batteries. Currently, various sodium-ion positive electrode materials with different crystal structures have been studied, such as layered oxide materials, polyanion materials, Prussian blue materials, organic materials, etc. The layered structure of layered oxide positive electrode materials provides good mechanical strength and thermal stability, and the performance can be improved by adjusting the interlayer spacing or chemical composition; but the cycle stability is poor, and the structure is prone to collapse or deformation, affecting the performance. The synthesis process of some layered oxides is complicated and the cost is high. Prussian blue materials have a high energy density and good chemical stability under a wide range of temperature and environmental conditions. The raw materials are abundant and cheap; but they are highly sensitive to moisture, and a large number of lattice defects and coordinated water are easily generated during the preparation process, resulting in performance degradation. In contrast, polyanions It has the advantages of stable structure and small volume change during repeated extraction / embedding of Na, and is the most important candidate material for practical applications. Iron-based mixed phosphate Na4Fe3(PO4)2P2O7 has a convenient 3D sodium ion transport pathway. The PO4 in the crystal structure 3- and P2O7 4- Dimers can reduce rotation and distortion, and therefore have the advantages of both phosphates and pyrophosphates; however, they usually have low electrical conductivity and are prone to form NaFePO4 impurity phases during the preparation process, which severely limits their industrial promotion. Summary of the invention

[0004] The main purpose of the present invention is to provide a carbon-composite nickel / cobalt / zinc medium-entropy doped sodium iron phosphate material, which adopts medium-entropy doping combined with carbon composite and other means to effectively improve the electronic conductivity of the obtained composite material and inhibit the formation of impure phase NaFePO4, shorten the ion diffusion path and electron transmission distance, so as to significantly improve the electrochemical performance of the obtained composite material.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate composite material, the stoichiometric formula of which is Na4Fe 3- 3x Ni x Co x Zn x (PO4)2P2O7 / C, x is 0.02-0.04; the composite material has a porous bowl-shaped structure.

[0007] Furthermore, the carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate composite material has a carbon content of 1-2% (wt%) and a specific surface area of ​​5-20 m 2 / g, and the pore size distribution range is 10-90nm.

[0008] Furthermore, the particle size of the carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate composite material is 0.1-10 μm.

[0009] The method for preparing the above-mentioned carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate composite material comprises the following steps:

[0010] 1) According to the stoichiometric formula Na4Fe 3-3x Ni x Co x Zn x (PO4)2P2O7 and designed carbon content Weigh the raw materials, disperse the weighed carbon source, sodium source, iron source, nickel source, cobalt source, zinc source and phosphorus source in water in proportion;

[0011] 2) subjecting the dispersion obtained in step 1) to ball milling and sand milling in sequence;

[0012] 3) spraying and granulating the dispersion obtained in step 2) to obtain a composite sodium iron phosphate precursor material;

[0013] 4) The obtained composite sodium iron phosphate precursor is calcined at high temperature in a protective atmosphere and crushed to obtain the carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material.

[0014] In the above scheme, the specific steps of preparing the raw material dispersion in step 1) are: adding a carbon source, a sodium source, an iron source, a nickel source, a cobalt source, a zinc source and a phosphorus source to water under oil bath and stirring conditions, and continuing to stir to fully dissolve the raw materials and evenly disperse them.

[0015] In the above scheme, the oil bath temperature is 60-80°C.

[0016] In the above scheme, in step 1), the molar ratio of the sodium source, iron source, nickel source, cobalt source, zinc source and phosphorus source is 4:3-3x:x:x:x:4; the amount of carbon source added (introduced C) is the theoretical NFPP product mass (designed Na4Fe 3-3x Ni x Co x Zn x (PO4)2P2O7 product mass) 4-15%.

[0017] Furthermore, in step 2), the ball milling time is 3-5 hours, and the ball milling speed is 300-500 r / min; the sand milling time is 2-4 hours, and the sand milling speed is 1000-2000 r / min.

[0018] In the above scheme, the sodium salt can be selected from at least one of sodium carbonate, disodium bicarbonate, sodium dihydrogen carbonate, sodium pyrophosphate, sodium chloride, sodium nitrate, sodium sulfate, sodium thiosulfate, sodium fluoride, etc.

[0019] In the above scheme, the iron salt can be selected from at least one of ferrous sulfate heptahydrate, ferric nitrate nonahydrate, ferrocene, ferric sulfate, ferric phosphate, ferrous phosphate, ferric citrate, ferric oxalate, ferric chloride hexahydrate, ferric acetylacetonate, and the like.

[0020] In the above scheme, the phosphorus source can be selected from at least one of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0021] In the above scheme, the nickel source is at least one of nickel oxide, nickel acetate, nickel hydroxide, nickel sulfate, nickel chloride, nickel nitrate, etc.; the cobalt source is at least one of cobalt oxide, cobalt hydroxide, cobalt sulfate, cobalt carbonate, cobalt oxalate, cobalt acetate, etc.; the zinc source is at least one of zinc oxide, zinc chloride, zinc acetate, zinc sulfate, zinc hydroxide, zinc carbonate, zinc acetate, etc.

[0022] In the above scheme, the carbon source is at least one of glucose, sucrose, polyvinyl pyrrolidone, citric acid, dopamine hydrochloride, polyethylene glycol, etc.

[0023] In the above scheme, in step 3), the inlet air temperature of the spray drying is 150-200°C, the outlet air temperature is 130-150°C, the feed rate is 10-15 mL / min, and the inlet pressure is 0.1-0.4 MPa.

[0024] Furthermore, in step 4), the calcination equipment is a tubular furnace; and the protective atmosphere is Ar, N2, Ar / H2 or N2 / H2.

[0025] The calcination is carried out in one step, with a heating rate of 2-5°C / min, a calcination temperature of 500-600°C, and a calcination time of 8-12h.

[0026] The present invention also provides the use of a carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material obtained by the above scheme in a positive electrode of a sodium ion battery.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The present invention adopts a medium entropy doping strategy based on nickel, cobalt, and zinc and combines it with carbon composite means, which can effectively inhibit the generation of impurities such as NaFePO4 during the calcination process and form a stable structure, showing a low volume change during the charge and discharge process, improving redox activity, improving electronic conductivity, and optimizing Na diffusion channels, thereby achieving rapid and stable sodium storage performance;

[0029] (2) The present invention adopts transition metal ion doping combined with spray granulation and calcination process, which can effectively change the electron density inside the material and enhance the NFPP cycle stability while regulating the microstructure of the composite material, so that the obtained sodium iron phosphate-based composite material can achieve excellent electrochemical performance;

[0030] (3) The porous hollow bowl-shaped structure of the prepared NFPP is conducive to the rapid penetration of electrolyte and the rapid transport of ions, further improving the electrochemical performance of the obtained composite material;

[0031] (4) The preparation method of the present invention is relatively simple, the raw materials are cheap and readily available, it is environmentally friendly, and can be mass-produced, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 (a) low magnification and (b) high magnification scanning electron microscope images of the carbon composite nickel / cobalt / zinc medium entropy-doped sodium iron phosphate material obtained in Example 1.

[0033] Figure 2 This is the X-ray diffraction pattern of the carbon composite nickel / cobalt / zinc entropy-doped sodium iron phosphate material obtained in Example 1.

[0034] Figure 3 This is a comparison chart of the rate performance of the composite materials obtained in Example 1 of the present invention and Comparative Example 1 used as positive electrode materials for sodium ion batteries.

[0035] Figure 4 This is a comparison chart of the long cycle stability of the composite materials obtained in Example 1 of the present invention and Comparative Example 1 when used as positive electrode materials for sodium ion batteries. DETAILED DESCRIPTION

[0036] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the comparative examples. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Unless otherwise specified, the equipment and reagents used in the present invention are conventional commercial products in the art.

[0037] Example 1

[0038] A carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material, the preparation method of which comprises the following steps:

[0039] 1) Add 60 mL of pure water to a beaker and heat to 80°C in an oil bath, then add 47.9836 g of sodium dihydrogen phosphate and stir to dissolve, add 81.735 g of ferrous sulfate heptahydrate and stir vigorously, and after uniform dispersion, add 0.354 g of nickel acetate, 0.354 g of cobalt acetate, and 0.367 g of zinc acetate in sequence, stir evenly, then add 3.049 g of citric acid and 3.049 g of sucrose, the carbon source, in sequence, and continue stirring for 30 min to make the dispersion reach a uniform state;

[0040] 2) placing the dispersion obtained in step 1) in a grinding jar, loading it into a planetary ball mill and milling it at a speed of 420 r / min for 4 h, then taking it out and transferring it to a sand mill and milling it at a speed of 1000 r / min for 3.5 h, and collecting the dispersion;

[0041] 3) The dispersion obtained in step 2) is spray-granulated by spray drying, with the air inlet temperature controlled at 180° C., the feed rate at 10 mL / min, and the spray atmosphere being air, to finally obtain a precursor dry powder;

[0042] 4) The precursor dry powder obtained in step 3) is placed in a porcelain boat, and under N2 protection conditions, the temperature is raised to 550°C at a rate of 5°C / min and calcined for 10 hours to obtain the carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material (denoted as Na4Fe 2.94 Ni 0.02 Co 0.02 Zn 0.02 (PO4)2P2O7 / C).

[0043] Example 2

[0044] A carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material, the preparation method of which comprises the following steps:

[0045] 1) Add 60 mL of pure water to a beaker and heat to 70°C in an oil bath, then add 80.901 g of ferrous sulfate heptahydrate and stir to disperse, add 47.9836 g of sodium dihydrogen phosphate and stir vigorously, and after the solution is evenly dispersed, add 0.530 g of nickel acetate, 0.531 g of cobalt acetate, and 0.550 g of zinc acetate, and after the solution is evenly dispersed, add 6.18 g of glucose and continue stirring for 30 min to make the dispersion reach a uniform state;

[0046] 2) placing the dispersion obtained in step 1) in a grinding jar, loading it into a planetary ball mill and milling it at a speed of 400 r / min for 5 h, then taking it out and transferring it to a sand mill and milling it at a speed of 1500 r / min for 3 h, and collecting the dispersion;

[0047] 3) The dispersion obtained in step 2) is spray-granulated by spray drying, with the air inlet temperature controlled at 190° C., the feed rate at 10 mL / min, and the spray atmosphere being air, to finally obtain a precursor dry powder;

[0048] 4) The precursor dry powder obtained in step 3) was placed in a porcelain boat, and heated to 550°C at a rate of 4°C / min and calcined for 10 h under Ar / H2 protective atmosphere to obtain a carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material (denoted as Na4Fe 2.91 Ni 0.03 Co 0.03 Zn 0.03 (PO4)2P2O7 / C).

[0049] Example 3

[0050] A carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material, the preparation method of which comprises the following steps:

[0051] 1) Add 60 mL of pure water to a beaker and heat to 60°C in an oil bath, then add 80.067 g of ferrous sulfate heptahydrate and 47.984 g of sodium dihydrogen phosphate and stir vigorously. After the solution is evenly dispersed, add 0.707 g of nickel acetate, 0.708 g of cobalt acetate and 0.734 g of zinc acetate. After the solution is evenly dispersed, add 6.19 g of citric acid and continue stirring for 30 min to make the dispersion uniform.

[0052] 2) placing the dispersion obtained in step 1) in a grinding jar, loading it into a planetary ball mill and milling it at a speed of 380 r / min for 5 h, then taking it out and transferring it to a sand mill and milling it at a speed of 1500 r / min for 2 h, and collecting the dispersion;

[0053] 3) The dispersion obtained in step 2) was spray granulated by spray drying, with the air inlet temperature at 190° C., the feed rate at 13 mL / min, and the spray atmosphere being air, to finally obtain a precursor dry powder;

[0054] 4) The precursor dry powder obtained in step 3) was placed in a porcelain boat, and heated to 500°C at a rate of 5°C / min and calcined for 10 h under N2 / H2 protective atmosphere to obtain a carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material (denoted as Na4Fe 2.88 Ni 0.04 Co 0.04 Zn 0.04 (PO4)2P2O7 / C).

[0055] Comparative Example 1

[0056] A carbon composite sodium iron phosphate (Na4Fe3(PO4)2P2O7 / C), the preparation method of which comprises the following steps:

[0057] 1) Add 60 mL of pure water to a beaker and heat to 80°C in an oil bath, then add 47.984 g of sodium dihydrogen phosphate and stir to dissolve, add 83.403 g of ferrous sulfate heptahydrate and stir vigorously, and after the solution is uniform, add 3.10 g of citric acid and 3.10 g of sucrose, and continue stirring for 30 min to make the dispersion uniform;

[0058] 2) placing the dispersion obtained in step 1) in a grinding jar, loading it into a planetary ball mill and milling it at a speed of 420 r / min for 4 h, then taking it out and transferring it to a sand mill and milling it at a speed of 1000 r / min for 3.5 h, and collecting the dispersion;

[0059] 3) The dispersion obtained in step 2) is spray-granulated by spray drying, with the air inlet temperature controlled at 180° C., the feed rate at 10 mL / min, and the spray atmosphere being air, to finally obtain a precursor dry powder;

[0060] 4) placing the precursor dry powder obtained in step 3) in a porcelain boat, heating to 550° C. at a rate of 5° C. / min and calcining for 10 h under N2 protection conditions; obtaining a carbon-composite sodium iron phosphate composite material.

[0061] Comparative Example 2

[0062] A carbon composite nickel / cobalt doped sodium iron phosphate material (Na4Fe 2.94 Ni 0.03 Co 0.03 (PO4)2P2O7 / C), the preparation method thereof comprises the following steps:

[0063] 1) Add 60 mL of pure water to a beaker and heat it to 70°C in an oil bath. Then add 81.735 g of ferrous sulfate heptahydrate and stir vigorously. After the solution is uniform, add 47.984 g of sodium dihydrogen phosphate. After the solution is evenly dispersed, add 0.530 g of nickel acetate and 0.531 g of cobalt acetate. After the solution is evenly dispersed, add 6.19 g of glucose again and continue stirring for 30 min to make the dispersion uniform.

[0064] 2) placing the dispersion obtained in step 1) in a grinding jar, loading it into a planetary ball mill and milling it at a speed of 400 r / min for 5 h, then taking it out and transferring it to a sand mill and milling it at a speed of 1500 r / min for 3 h, and collecting the dispersion;

[0065] 3) The dispersion obtained in step 2) is spray-granulated by spray drying, with the air inlet temperature controlled at 190° C., the feed rate at 10 mL / min, and the spray atmosphere being air, to finally obtain a precursor dry powder;

[0066] 4) placing the precursor dry powder obtained in step 3) in a porcelain boat, heating to 550°C at a rate of 4°C / min and calcining for 10 hours under N2 / H2 protective atmosphere; obtaining a carbon-composite nickel / cobalt dual-doped sodium iron phosphate material.

[0067] Comparative Example 3

[0068] A carbon composite cobalt / zinc doped sodium iron phosphate material (Na4Fe 2.94 Co 0.03 Zn 0.03 (PO4)2P2O7 / C), the preparation method thereof comprises the following steps:

[0069] 1) Add 60 mL of pure water to a beaker and heat to 60°C in an oil bath, then add 47.984 g of sodium dihydrogen phosphate and stir vigorously. After the solution is uniform, add 81.735 g of ferrous sulfate heptahydrate. After the dispersion is uniform, add 0.531 g of cobalt acetate, 0.550 g of zinc acetate and 6.2 g of citric acid, and continue stirring for 30 min to make the dispersion uniform.

[0070] 2) placing the dispersion obtained in step 1) in a grinding jar, loading it into a planetary ball mill and milling it at a speed of 380 r / min for 5 h, then taking it out and transferring it to a sand mill and milling it at a speed of 1500 r / min for 2 h, and collecting the dispersion;

[0071] 3) The dispersion obtained in step 2) was spray granulated by spray drying, with the air inlet temperature at 190° C., the feed rate at 13 mL / min, and the spray atmosphere being air, to finally obtain a precursor dry powder;

[0072] 4) placing the precursor dry powder obtained in step 3) in a porcelain boat, heating to 500° C. at a rate of 5° C. / min and calcining for 10 h under N2 protection conditions; obtaining a carbon-composite cobalt / zinc dual-doped sodium iron phosphate material.

[0073] Comparative Example 4

[0074] A carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material (Na4Fe 2.94 Ni 0.02 Co 0.02 Zn 0.02 (PO4)2P2O7 / C), the preparation method thereof comprises the following steps:

[0075] 1) Add 60 mL of pure water to a beaker and heat it to 60 ° C in an oil bath, then add 71.1067 g of ferric nitrate and stir vigorously. After the solution is evenly dispersed, add 42.396 g of sodium carbonate and 46.010 g of diammonium phosphate. After the solution is evenly dispersed, add 0.354 g of nickel acetate, 0.354 g of cobalt acetate and 0.367 g of zinc acetate in sequence. After stirring evenly, add 3.049 g of citric acid and 3.049 g of sucrose, the carbon source, in sequence, and continue stirring for 30 min to make the dispersion reach a uniform state;

[0076] 2) placing the dispersion obtained in step 1) on a heating stirrer, raising the temperature to 90° C. while continuously stirring, and continuously stirring until the water evaporates to form a gel state; then transferring to a 100° C. forced air drying oven to completely evaporate the remaining water;

[0077] 4) The dried composite sodium iron phosphate precursor powder obtained in step 3) is placed in a crucible, and heated to 550° C. at a rate of 5° C. / min and calcined for 10 h under a N2 / H2 protective atmosphere to obtain a carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate composite material.

[0078] The differences between Comparative Examples 1, 2, and 3 and Example 1 are that Comparative Example 1 is undoped, Comparative Example 2 is only doped with nickel / cobalt, Comparative Example 3 is doped with cobalt / zinc, and Comparative Example 4 uses a sol-gel method to prepare the precursor.

[0079] The carbon composite nickel / cobalt / zinc doped composite sodium iron phosphate prepared in Example 1 was observed for morphology, and the scanning electron microscope results are as follows: Figure 1 As shown by Figure 1 It can be seen that the obtained product has a hollow bowl-shaped porous structure. After testing, its carbon content is 1.15wt% and its specific surface area is 5.26m 2 / g, and the pore size distribution range is 10-90nm.

[0080] The crystal structure of the carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate composite material prepared in Example 1 and Comparative Example 1 was tested, and the X-ray diffraction results are as follows: Figure 2 As shown, it can be seen that the diffraction peak of the product obtained in the present invention is consistent with the diffraction peak of the NaCo3(PO4)2P2O7 standard card (the NFPP phase currently corresponds to the NaCo3(PO4)2P2O7 standard card); the NaFePO4 diffraction peak in the product obtained in Example 1 is significantly weakened relative to that in Comparative Example 1.

[0081] Compared with the comparative example 1, the corresponding X-ray diffraction results of the sodium iron phosphate composite material obtained in comparative example 2-4 have no significant changes, and the diffraction peak of the impurity NaFePO4 has no significant weakening. The sodium iron phosphate composite material obtained in comparative example 2-4 is used as the positive electrode material to assemble the composite sodium ion battery by the same method. In the voltage range of 1.7-4.3V, the electrochemical performance and long cycle stability at different current densities are not significantly improved compared with comparative example 1. The following mainly compares the sodium ion battery assembled with the composite material prepared in Example 1 as the positive electrode material and the specific steps are as follows:

[0082] 1) The composite materials obtained in Example 1 and the comparative example were respectively mixed with super P and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 and dispersed in N-methyl-2-pyrrolidone (NMP) to form a uniform slurry, and the obtained slurry was evenly coated on an aluminum foil to prepare an electrode, and the electrode was dried in a vacuum drying oven at 120 degrees, and the electrode was cut into an electrode sheet with a diameter of 10 mm for standby use;

[0083] 2) Using 1.0M NaPF6 in PC (propylene carbonate) as the electrolyte, a glass fiber diaphragm (Whatman GF / D) as the diaphragm, and metallic sodium as the counter electrode, they were assembled in an argon-filled glove box in the order of: negative electrode metal shell → sodium metal sheet → diaphragm → positive electrode → gasket → spring → metal positive electrode shell, to obtain a carbon composite nickel / cobalt / zinc doped composite sodium iron phosphate composite sodium ion battery assembled using the composite material of Example 1 as the positive electrode material, and a composite sodium ion battery assembled using the composite material of Comparative Example 1 as the positive electrode material.

[0084] Figure 3 The performance comparison diagram of the sodium ion battery positive electrode obtained by using the composite material prepared by Example 1 of the present invention and Comparative Example 1 under different current densities in the voltage range of 1.7 to 4.3V. It can be seen from the figure that the carbon composite nickel / cobalt / zinc doped composite sodium iron phosphate composite sodium ion battery positive electrode material prepared by Example 1 has better rate performance than the composite sodium ion battery negative electrode material prepared by Comparative Example 1. The specific capacity of Example 1 at 0.2C is 106mAh g -1 , the specific capacity is 93.5 mAh g at 10C -1 , the specific capacity is 91.36 mAh g at 20C -1 , better than comparative example 1 (91.5 mAh g -1 、80.2mAh g -1 and 75.2mAh g -1 ).

[0085] Figure 4The figure is a comparison of the long cycle stability of the composite materials prepared in Example 1 of the present invention and in Comparative Example 1 for use as positive electrode materials for sodium ion batteries. It can be seen from the figure that the carbon composite nickel / cobalt / zinc doped composite sodium iron phosphate positive electrode material prepared in Example 1 has better cycle stability than the composite sodium ion battery positive electrode material prepared in Comparative Example 1. Example 1 achieved 89 mAh g after 3500 cycles at 10C. -1 The stable charging capacity of the battery is 95.7% of the initial cycle, which is better than that of Comparative Example 1 in terms of capacity retention and cycle stability.

[0086] The above properties indicate that the prepared carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate positive electrode material has excellent rate performance and cycle performance, can effectively inhibit the formation of impure phase NaFePO4 and regulate the material conductivity, and provides a new idea for the preparation of electrochemical properties of sodium ion battery positive electrode materials by changing the configurational entropy, and can meet industrial needs in mass production.

[0087] For those skilled in the art, it is easy to improve and embellish the present invention without departing from the technology of the present invention, and these improvements and embellishments also fall within the scope of protection of the present invention. The present invention is not limited to the above-mentioned embodiments, and any changes within the claims of the present invention are covered within the scope of protection.

Claims

1. A carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material, characterized in that: The carbon composite nickel / cobalt / zinc entropy doped sodium iron phosphate material has a stoichiometric formula of: Na4Fe 3-3x Ni x Co x Zn x (PO4)2P2O7 / C, x value is 0.02-0.04; it has a bowl-shaped porous structure.

2. The carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material according to claim 1, characterized in that: in, Carbon content is 1-2wt%; specific surface area is 5-20m 2 / g, pore size is 10-90nm.

3. The carbon-composite nickel / cobalt / zinc-doped composite sodium iron phosphate composite material according to claim 1, characterized in that: The particle size of the carbon composite nickel / cobalt / zinc entropy-doped sodium iron phosphate material is 0.1-10 μm.

4. The method for preparing the carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material according to claim 1, characterized in that: The steps include: 1) According to the stoichiometric formula Na4Fe 3-3x Ni x Co x Zn x (PO4)2P2O7 and designed carbon content Weigh the raw materials, disperse the weighed carbon source, sodium source, iron source, nickel source, cobalt source, zinc source and phosphorus source in water in proportion; 2) subjecting the dispersion obtained in step 1) to ball milling and sand milling in sequence; 3) spraying and granulating the dispersion obtained in step 2) to obtain a composite sodium iron phosphate precursor material; 4) The obtained composite sodium iron phosphate precursor is calcined at high temperature in a protective atmosphere and crushed to obtain the carbon composite nickel / cobalt / zinc medium entropy doped sodium iron phosphate material.

5. The preparation method according to claim 4, characterized in that: The amount of carbon source added is 4-10% of the theoretical mass of the sodium iron phosphate-based product.

6. The preparation method according to claim 4, characterized in that: The nickel source is at least one of nickel oxide, nickel acetate, nickel hydroxide, nickel sulfate, nickel chloride, and nickel nitrate; the cobalt source is at least one of cobalt oxide, cobalt hydroxide, cobalt sulfate, cobalt carbonate, cobalt oxalate, and cobalt acetate; and the zinc source is at least one of zinc oxide, zinc chloride, zinc sulfate, zinc hydroxide, zinc carbonate, and zinc acetate.

7. The preparation method according to claim 4, characterized in that: In step 2), the ball milling adopts a rotation speed of 300-500 rpm / min for 3-5 hours; the sand milling adopts a rotation speed of 1000-2000 rpm / min for 2-4 hours.

8. The preparation method according to claim 4, characterized in that: In step 3), spray drying is carried out by stirring and feeding, the inlet air temperature is 150-200°C, the outlet air temperature is 130-150°C, the feed rate is 10-15mL / min, and the inlet pressure is 0.1-0.4MPa.

9. The preparation method according to claim 4, characterized in that: The temperature used for high temperature calcination is 500-600°C and the time is 8-12h.

10. Use of the carbon-composite nickel / cobalt / zinc medium-entropy doped sodium iron phosphate material according to any one of claims 1 to 3 or the carbon-composite nickel / cobalt / zinc medium-entropy doped sodium iron phosphate material prepared by the preparation method according to any one of claims 4 to 9 in the positive electrode of a sodium ion battery.